Prawo a gospodarka - Komar, Andrzej (Wydział Prawa i Administracji UAM, 1982)
The article discusses the role of law in shaping of the economic relations. It presents relations between law and economy and the possibilities of law in the domain of economy. It has been underlined that there are explicit limits of these possibilities. Trespassing upon them causes the degradation of both law and economy. In the article, the author has analysed the Seym bills of social — economic planning, of prices, of the financial economy of state-owned business, of taxation of state-owned bussines and of banking law. At the same time it has been indicated that these bills do not constitute the economic reform because they lack some kind of a general and common conception.
Law and Economy